Strategi layanan bimbingan dan konseling untuk meningkatkan kepercayaan diri korban kekerasan dalam rumah tangga - Aulia Dayu Kholifah; Siti Bahiroh (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study describes the domestic violence case that increases every year, making this case need to be addressed immediately because the its impact can cause misery to the victims. This study aims to determine how the strategies of guidance and counseling service to increase the confidence of domestic violence victims. The subjects in this study were Social Workers, Counselors, Psychologists and 3 assisted people who experienced domestic violence and underwent rehabilitation at Center for Women's Social Protection and Rehabilitation. The results of this study showed that guidance and counseling strategies had a very important role in the process of building the self-confidence of domestic violence victims. The strategies of guidance and counseling service provided were: counseling guidance from social workers, counselors and psychologists, skills guidance and religious guidance.